2017
DOI: 10.1002/cbic.201600532
|View full text |Cite
|
Sign up to set email alerts
|

Motuporamine Derivatives as Antimicrobial Agents and Antibiotic Enhancers against Resistant Gram‐Negative Bacteria

Abstract: Dihydromotuporamine C and its derivatives were evaluated for their in vitro antimicrobial activities and antibiotic enhancement properties against Gram‐negative bacteria and clinical isolates. The mechanism of action of one of these derivatives, MOTU‐N44, was investigated against Enterobacter aerogenes by using fluorescent dyes to evaluate outer‐membrane depolarization and permeabilization. Its efficiency correlated with inhibition of dye transport, thus suggesting that these molecules inhibit drug transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…[1][2][3] Since 1928, thousands of compounds that target essential pathwaysh ave been isolated from naturals ources. Polyamine natural products such as squalamine, [5,6] ianthelliformisamines (B and C), [7] and motuporamines [8] are known to target bacterial cell membraneswith modest activity ( Figure 1). Antibiotic resistance is an issue of great concern that has attracted the attention of health agencies, media, and global leaders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Since 1928, thousands of compounds that target essential pathwaysh ave been isolated from naturals ources. Polyamine natural products such as squalamine, [5,6] ianthelliformisamines (B and C), [7] and motuporamines [8] are known to target bacterial cell membraneswith modest activity ( Figure 1). Antibiotic resistance is an issue of great concern that has attracted the attention of health agencies, media, and global leaders.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Resistance to membrane-active compounds requires either an increase in efflux pumps or am ajor change in membrane structure, which in turn influencest he permeability barrier,i ncreasing susceptibility to hydrophobic antibiotics. Polyamine natural products such as squalamine, [5,6] ianthelliformisamines (B and C), [7] and motuporamines [8] are known to target bacterial cell membraneswith modest activity ( Figure 1). Therefore, we and others were able to demonstrate the importance of the amphiphilicity of the molecules as well as the crucial nature of the polyamine group linked to aw ell-chosen lipophilic molecule to encounter interesting antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…110 Finally, the results of various tests concluded that the permeabilization of the bacterial membrane in E. aerogenes EA289 by motuporamine derivatives was related to the change in the transmembrane electrical potential leading to altered proton homeostasis. 112 In this same area, a series of ianthelliformisamines A, B, and C (40-42) were identified, synthesized and used to enhance Gram-negative bacteria susceptibility to hydrophobic antibiotics. 113 Thus, natural and synthetic derivatives were used to restore the activity of doxycycline against Enterobacter aerogenes EA289, P. aeruginosa PAO1, and K. pneumoniae KPC2 ST258.…”
Section: Concerning the Observed Inhibition Of The Pump A Potent Explanation Is Based On The Escherichiamentioning
confidence: 99%
“…Glucose‐triggered 1,2′‐diNA efflux assays : [27] Bacteria were grown to stationary phase, collected by centrifugation, and resuspended to OD 600 =0.25 in PPB (20 mM, pH 7.2) supplemented with carbonyl cyanide m ‐chlorophenyl hydrazone (CCCP, 5 μM), and incubated overnight with 1,2’‐dinaphthylamine (1,2’‐diNA, 32 μM) at 37 °C. Before addition of compound 14 (100 μM), the cells were washed with phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%